2022
DOI: 10.1371/journal.pone.0262994
|View full text |Cite
|
Sign up to set email alerts
|

Impulse dispersion of aerosols during playing wind instruments

Abstract: Musical activities, especially singing and playing wind instruments, have been singled out as potentially high-risk activities for the transmission of SARS CoV-2, due to a higher rate of aerosol production and emission. Playing wind instruments can produce condensation, droplets of saliva, and aerosol particles, which hover and spread in the environmental air’s convectional flows and which can be potentially infectious. The aim of this study is to investigate the primary impulse dispersion of aerosols that tak… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
3
8
1
Order By: Relevance
“…When playing in the high octave, at the end of the task, the clouds showed medians of 1.06 m to the front (x-direction) and .57 m diameter laterally (y-direction), with maxima of x: 1.35 m and y: .97 m). Compared to the dispersion values of other instruments in a previous study with the same experimental setup 14 , without safety device at the end of the task, the straight-built recorder produced larger distances than the winding-built trumpet (the trumpet values were medians: x: .86 m and y: .3 m; maxima: x: 1.20 m and y: .52 m). Even though the mechanism of the recorder is somewhat similar to the flute, dividing the airflow from the windway above the block at the labium, the generated jet stream of aerosols did not go as far as for the flutes (flutes’ medians: x: 1.51 m, y: .64 m; maxima: x: 1.88 m, y: 1.23 m).…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…When playing in the high octave, at the end of the task, the clouds showed medians of 1.06 m to the front (x-direction) and .57 m diameter laterally (y-direction), with maxima of x: 1.35 m and y: .97 m). Compared to the dispersion values of other instruments in a previous study with the same experimental setup 14 , without safety device at the end of the task, the straight-built recorder produced larger distances than the winding-built trumpet (the trumpet values were medians: x: .86 m and y: .3 m; maxima: x: 1.20 m and y: .52 m). Even though the mechanism of the recorder is somewhat similar to the flute, dividing the airflow from the windway above the block at the labium, the generated jet stream of aerosols did not go as far as for the flutes (flutes’ medians: x: 1.51 m, y: .64 m; maxima: x: 1.88 m, y: 1.23 m).…”
Section: Discussioncontrasting
confidence: 54%
“…This study investigates the impulse dispersion of aerosols during playing the soprano recorder and three potential safety devices. In general, it was found that the impulse dispersion characteristics were comparable to those of the clarinets 14 but not flutes, and that a suction funnel can reduce the aerosol dispersion significantly, while other devices covering the instrument were problematic concerning the aerosol dispersion and/or practical implementation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations